EGFR, p16INK4a and E-cadherin immuno-histochemistry and EGFR point mutations analyses in invasive cervical cancer specimens from Moroccan women - El Hamdani, W.; Amrani, M.; Attaleb, M.; Laantri, N.; Ennaji, M. M.; Khyatti, M.; El Mzibri, M. (Cellular and Molecular Biology, 2010)
The involvement of human papillomavirus in the development of cervical cancer has been firmly established. However, better management of cervical cancer rests on good diagnosis and an effective therapy. In this study we evaluated the frequency of point mutations in epidermal growth factor receptor (EGFR) for future use of tyrosine kinase inhibitors in clinical treatment and to assess the use of EGFR, p16INK4a and E-cadherin as biomarkers in cervical cancer diagnosis with immunohistochemistry. Fifty-three patient specimens of cervical cancer were analysed for HPV infection, for EGFR mutations in exons 18 through 21, and for expression of EGFR, p16INK4a and E-cadherin by immunostaining. Results showed that 79.24% of the cases (42/53) are HPV positive and the HPV types more closely associated with risk are HPV 16 and 18. In all 53 analysed specimens, any mutation affecting the EGFR kinase domain in exons 18 through 21 was observed. Expressions of EGFR, p16INK4a and E-cadherin were detected in 88,67% (47/53), 92,45% (49/53) and 79,24% (42/53) of analysed specimens respectively. Thus, EGFR, p16INK4a and E-cadherin would be excellent tools for IHC analysis during the cervical cancer development. EGFR and p16INK4a can be used for early diagnosis and E-cadherin for cancer progression and cell migration. However, treatment of cervical cancer with TKIs may not be effective and the identification of other EGFR inhibitors is needed.